Circinate Balanitis in a Patient with Sexually Acquired Reactive Arthritis: Clinical Images - Shivani Deepak Jangid; Bhushan Madke (Journal of Clinical and Diagnostic Research)
A 37-year-old male patient presented to Dermatology Out Patient Department (OPD) with complaints of multiple hyperkeratotic plaques over his entire body, bilateral palms, and soles for one year. The lesions were associated with low back pain and bilateral knee joint pain. The lesions were also associated with onycholysis and subungual debris in the nails of bilateral hands and feet. The patient complained of occasional dysuria and purulent discharge in urine. The patient also had a history of sexual contact six months before the onset of lesions. On further examination of the genitals, the penile region revealed multiple asymptomatic superficial erosions that coalesce to form a sharply demarcated, serpiginous pattern [Table/Fig-1]. Multiple hyperkeratotic papules and plaques with exfoliation of skin were present over the sole, suggestive of keratoderma blennorrhagicum [Table/Fig-2].